How do you solve 2(4x + 2) - 8 = 4(x + 3) ?

1 Answer
Feb 12, 2017

See the entire solution process below:

Explanation:

First, expand the terms in parenthesis on each side of the equation:

(2 xx 4x) + (2 xx 2) - 8 = (4 xx x) + (4 xx 3)

8x + 4 - 8 = 4x + 12

8x + -4 = 4x + 12

8x -4x = 12+4

8x = 4x +16

Next, subtract color(red)(4x) from each side of the equation to isolate the x term while keeping the equation balanced:

8x - color(red)(4x) = 4x + 16 - color(red)(4x)

(8 - 4)x = 4x - color(red)(4x) + 16

4x = 0 + 12

4x = 16

Now, divide each side of the equation by color(red)(4) to solve for x while keeping the equation balanced:

(4x)/color(red)(4) = 16/color(red)(4)

(color(red)(cancel(color(black)(4)))x)/cancel(color(red)(4)) = 4

x = 4